Program Kegiatan Ilqo’ Mufrodat di Pondok Modern Darussalam Gontor Kampus 7 Kalianda Lampung Selatan: Menggunakan Model Evaluasi Kirkpatrick - Fatkhur Rozaq Muhajir; Raja Firmansyah; Putra Gilang Prayoga; Syaifudin Syaifudin (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2022)
This study aims to see how the ilqo' mufrodat activity program runs. This study focused on Pondok Modern Darussalam Gontor, Campus 7 Kalianda, South Lampung using the Kirkpatrick evaluation model. The method used in this study is a qualitative research method with an evaluation research design by observing, interviewing, and reviewing program implementation documents. Sources of information were obtained through interviews with ilqo' mufrodat program supervisors, activity supervisors, and students. The results of the research on the components being evaluated show that the evaluation of the Kirkpatrick model from Pondok Modern Darussalam Gontor Campus 7 Kalianda, South Lampung has been successfully carried out. This can be seen from the existence of four things in the evaluation: evaluation of reactions, evaluation of learning, evaluation of behavior, evaluation of results. The results of this study indicate that the program is running effectively. As for the hours of sleep of students at night, more attention must be paid, because this will have implications for student activities the next day.